An Overview on Nature Function in Relation with Spread of Omicron-Covid-19: Where Will the Next Pandemic Begin and Why the Amazon Forest Offers Troubling Clues - (:unkn) unknown (AMG Transcend Association, 2022)
The effect of COVID-19 vaccination also depends on the population that accepts vaccines. Improving the COVID-19 vaccination methods will be tremendous to human health and the world economy. So, in this work, we use an interdisciplinary knowledge from climates, social sciences, geography, jungle, forestry and wood industry, genetic analysis, and computational biophysics, including artificial intelligence and docking simulation. The emergence of the omicron variant raises serious concerns because of the initial observation of a significant growth advantage compared to the Delta, lambda, beta, and gamma variants. Although the omicron variant preliminary observed in the EU/EEA and Asian countries depend on travel, several are now observed as parts of pandemic clustering in this zoon. Since, even if the severity of the disease is lower compared with other variants, particularly Delta, the fast transmissibility and resulting exponential growth of cases will soon outweigh any benefits of a potentially reduced severity. This research showed that though omicron covid-19 death cases are less severe than Delta, Omicron will be an important base for the emergence of new further variants through huge mutations in the future, which some are so dangerous. Due to the wet climate, the Amazon jungle is a suitable substrate for emerging any further corona variants.
Keywords: 15. Life on land; 3. Good health